2003
DOI: 10.1002/eqe.283
|View full text |Cite
|
Sign up to set email alerts
|

Experimental identification of the vibration modes of liquid‐filled conical tanks and validation of a numerical model

Abstract: SUMMARYTruncated conical-shaped shells are widely used as containment vessels in elevated water tanks. In the aftermath of earthquakes, water tanks play a vital role in supplying the water needed for extinguishing ÿres that usually occur during these catastrophic events. As such, special attention has to be given when designing water tanks in order to assure safety and functionality of these structures during a seismic event. To the best of the authors' knowledge, this paper reports the ÿrst experimental progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The shell vibration was determined assuming zero hydrodynamic pressure at the liquid free-surface. The validity of this analytical model was verified in a later experimental study carried out by Sweedan and El Damatty (2002) on a small-scale purely conical tank.…”
Section: Response Of Elevated Tanksmentioning
confidence: 67%
“…The shell vibration was determined assuming zero hydrodynamic pressure at the liquid free-surface. The validity of this analytical model was verified in a later experimental study carried out by Sweedan and El Damatty (2002) on a small-scale purely conical tank.…”
Section: Response Of Elevated Tanksmentioning
confidence: 67%
“…The coordinates with the maximum value represent the displacement of the object caused by an external force. In Equations (1) and (2), f (x i , y j ) and g(x i , y j ) represent the gray level values of the windows before and after deformation, respectively.…”
Section: Image Correlation Methodsmentioning
confidence: 99%
“…Thus, to evaluate the safety of liquid storage tanks, it is important to identify their dynamic characteristics. Many studies have been conducted to identify the dynamic characteristics of liquid storage tanks, and it was found that their dynamic characteristics are affected by their geometry and materials, the types of fluids stored in them, their water level, and the excitation force applied on them [2][3][4][5]. When dynamic loads such as earthquakes are applied to a liquid storage tank, the hydrodynamic pressure acting on the structure and the dynamic behavior of the structure can be significantly amplified due to the interaction between the structure and the liquid inside it.…”
Section: Introductionmentioning
confidence: 99%
“…Although the active vibration control of beams, plates and cylindrical shells has received many people's attention, to our knowledge, few people have studied the active vibration control of conical shells. Conical shells are widely used as important structural components in many engineering fields Liew, 1995, 1996;Sweedan and El Damatty, 2003;Senthil Kumar and Ganesan, 2008;Kayran and Yavuzbalkan, 2009;Sofiyev, 2009;Tornabene, 2009;Kerboua et al, 2010). Normally, the equation of motion of the conical shell is very complicated and some coefficients of the equation of motion are variables (Lam and Li, 1999b), which makes it difficult to analytically solve the equation of motion of the conical shell.…”
Section: Introductionmentioning
confidence: 99%